ORCHIDACEAE NOVAE VEL MINUS COGNITAE - H. G. JONES (REINWARDTIA, 1974)
The new species Cymbidium intermedium from India is described, and critical morphological and nomentlatural notes on the Asiatic  Cirrho-petabtm putidmn as well as the American Hoff-mannseggella crispilabia and Encyclia fragrana are presented.